2016
DOI: 10.1038/srep35965
|View full text |Cite
|
Sign up to set email alerts
|

One compound of saponins from Disocorea zingiberensis protected against experimental acute pancreatitis by preventing mitochondria-mediated necrosis

Abstract: Acute pancreatitis (AP) is a painful inflammatory disorder of the exocrine pancreas, ranking as the most common gastrointestinal reasons for hospitalization with no specific therapy currently. Diosgenyl saponins extracted from natural products and diosgenin or its derivatives have been shown to exert anti-inflammatory effects in various diseases. However, the therapeutic effects of diosgenyl saponins from Dioscorea zingiberensis C. H. Wright in AP have not yet been determined. Five compounds were extracted and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…Therefore, we hypothesized that Dydio could prevent excessive inflammatory responses and thus mitigate distant organ injury associated with pancreatitis. As ALI is one of the most frequent distant organ injuries associated with severe AP (Zhang et al, ), we then examined the effects of Dydio on ALI in our models of AP. Treatment with Dydio (5 and 10 mg·kg −1 ) significantly reduced lung MPO in all the models of AP (Tauro, CER and FAEE) (Figure A).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, we hypothesized that Dydio could prevent excessive inflammatory responses and thus mitigate distant organ injury associated with pancreatitis. As ALI is one of the most frequent distant organ injuries associated with severe AP (Zhang et al, ), we then examined the effects of Dydio on ALI in our models of AP. Treatment with Dydio (5 and 10 mg·kg −1 ) significantly reduced lung MPO in all the models of AP (Tauro, CER and FAEE) (Figure A).…”
Section: Resultsmentioning
confidence: 99%
“…We have recently reported that diosgenyl saponins isolated from from Disocorea zingiberensis C. H. Wright, particularly 26‐O‐β‐D‐glucopyranosyl‐3β, 22α, 26‐trihydroxy‐25(R)‐furosta‐5‐en‐3‐O‐[α‐L‐rhamnopyranosyl‐(1→4)]‐β‐D‐glucopyranoside (Compound 1 ) protected against pancreatic acinar injury and three models of experimental AP (Zhang et al, ), providing the impetus to further isolate and identify the most potent compound of the diosgenyl saponins for protection against AP. However, extracting diosgenyl saponins from D. zingiberensis C. H. Wright or other natural sources is not ideal for medicinal chemistry modifications, as the process of isolation is time‐consuming and purification is challenging.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it also significantly reduced histological pancreatic injury in mice (Zhang et al. 2016 ). Remarkably, the potential mechanism of this compound is still unclear, and much more research is still needed.…”
Section: The Potential Mechanisms Of Phytochemicals In the Attenuatio...mentioning
confidence: 99%